Change is always as a last resort change in habits of thought: for a new biodiversity of cognition in the face of today's crisis. (13th July 2021) - Graupe, Silja
The present crisis has revealed that around the globe we are often only able to react to crises when it is (almost) too late. This paper addresses and explains the mono-structure of thought that has led to this predicament and delineates a new model of cognition capable of creating a new biodiversity of thought and action, especially in the economic sphere. With this, future crises may not only be overcome but may also contribute be avoided altogether. This paper offers a vision which does not provide ready-made answers but rather aims more fundamentally at opening up a wholly new imaginative scope for the possible.